Understanding the Psychological Well-being of International Students at a Private University in Surabaya, Indonesia - Salim, Hotimah Masdan; Salamy, Achmad Yarziq Mubarak Salis; Afridah, Wiwik; Budury, Syiddatul; Hanik, Umi (KnE Social Sciences, 2025)
Amidst the backdrop of globalization, there has been a marked increase in international student enrollment across global higher education institutions. This study examines the psychological well-being of international students at a private university in Surabaya, Indonesia, focusing on the unique challenges and support systems available during their educational journey. The study used a mixed-methods approach, combining quantitative assessment of well-being through standardized scales and qualitative interviews to capture personal narratives. The study sample consisted of 15 international students from various countries, providing diverse perspectives on the acculturation process and its impact on mental health. The results showed that factors such as cultural adjustment, language barriers, social support from peers, and the availability of university-led mental health services significantly influenced the overall well-being of these students. The study findings showed that while most students experienced initial stress and anxiety, those who engaged with available support showed marked improvements in their psychological well-being over time. This study underscores the importance of targeted support services for international students to enhance their academic and social experiences.